PROFIL LITERASI SISWA KELAS VII SMP NEGERI 11 KOTA BENGKULU TAHUN AJARAN 2016/6017 - Rahmat Hidayat (Universitas Bengkulu, 2018)
The purpose of this study is to describe the profile of class VII students of SMP Negeri 11 Kota Bengkulu academic year 2016/2017. This research uses quantitative descriptive method. Data in this research is data type and data in this research is student of class VII. Technique of writing data in this research is survey, a questionnaire. Data analysis technique is a percentage technique that is digging the data, calculate the percentage and analyze the data. Validity test using content validity and visible validity. The result of the research shows that the literacy profile of the students of VII SMP Negeri 11 Kota Bengkulu in the academic year 2016/2017 in 75% abituation aspect is appropriate but must be improved again and all the school should be involved in literacy activities. The literacy profile in making 78% decisions is appropriate but should be corrected again. The students' literacy profile in the learning aspect as a whole is 77% fit but must be folded again in critical thinking even though it is not included in the quality Keywords: profile, literacy